The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.9790/0853-1606055962
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Various Treatment Modalities for Amoebic Liver Abscess

Abstract: The management of liver abscess has changed with significant reduction in mortality and morbidity after the advent of imaging modalities and antibiotics. The present study was conducted to study the effectiveness of various treatment modalities for amoebic liver abscess including the percutaneous catheter drainage procedure in these patients. We concluded that amoebic liver abscess need drainage either by single or multiple aspirations failing which percutaneous catheter drainage should be done.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…The study observed high success rates for both pyogenic (90%, n=54) and amoebic (95%, n=38) liver abscesses, affirming the efficacy of current treatment modalities [15,16]. However, the recurrence rate within six months was notably higher for pyogenic abscesses (8.3%, n=5) compared to amoebic ones (2.5%, n=1) [17,18].…”
Section: Treatment Outcomes and Modalitiesmentioning
confidence: 57%
“…The study observed high success rates for both pyogenic (90%, n=54) and amoebic (95%, n=38) liver abscesses, affirming the efficacy of current treatment modalities [15,16]. However, the recurrence rate within six months was notably higher for pyogenic abscesses (8.3%, n=5) compared to amoebic ones (2.5%, n=1) [17,18].…”
Section: Treatment Outcomes and Modalitiesmentioning
confidence: 57%